PENGARUH PENERAPAN UNDANG-UNDANG NOMOR 9 TAHUN 2017 DAN KESADARAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI PADA UMKM DI KOTA MANADO - Pawama, Shinta D.; Warongan, Jessy D. L. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2022)
<span style="font-size: 12pt; font-family: ’Times New Roman’; color: #202124; background-color: transparent; font-weight: 400; font-style: italic; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;">The effect of the implementation undang-undang no 9 tahun 2017 and taxpayer awareness of personal person taxpayerâ€™s obedience at MSMEs in Manado city. (Under the supervisor of Jessy D. L. Warongan). <span style="font-size: 12pt; font-family: ’Times New Roman’; color: #202124; background-color: transparent; font-weight: 400; font-style: italic; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;">The low level of tax payment compliance by personal person taxpayers at MSMEs in Manado is a serious problem and must be handled jointly by the government and the taxpayers themselves, to create personal person awareness and obedience to existing tax laws. The study is aimed of this research are to analysis and prove empirically the effects of the application of law number 9 of 2017 and taxpayer awareness in increasing personal person taxpayerâ€™s obedience on MSMEs in Manado. The collection method used questionnaires and by using multiple linear regression method to test the hypothesis using SPSS 25th version. The population was taken on personal person taxpayers of SMEs in the Manado city with total 15,000 personal person taxpayers in MSMEs. The results show that both the implementation undang-undang no 9 tahun 2017 and taxpayer awareness have a positive and significant effect on the personal person taxpayerâ€™s obedience on MSMEs in Manado city.